2013
DOI: 10.2478/nbec-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Synthetic Dyes Onto River Sediments: A Laboratory Study

Abstract: This work deals with sorption of cationic synthetic dye thioflavine T (ThT) onto the river sediment obtained from the Váh River under conditions of batch and column system using spectrophotometric methods. We found that sorption of ThT onto river sediment was a rapid process with reaching of concentration equilibrium within 2 h of interaction. The values of distribution coefficient (DC) defined as concentration ratio [ThT]sediment : [ThT]solution were linearly increased with increasing concentration of river s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Freundlich isotherms model also satisfactorily described the sorption of Thioflavin dye in sediments taken from the banks of the Váh River, in Šaľa city, Slovak Republic (Bachratá et al, 2013), and of Basic Yellow X-5GL, Basic Red 13, Direct Blue 86, Vat Yellow 2 and Mordant Black 11 dyes in sediments from the Qinghe River (Liu et al, 2001). Other studies also reported a good correlation of the Freundlich equation with experimental data of dye sorption in soils, such as the Acid Yellow 23 (Dawodu and Akpomie, 2016), Basic Blue 9 (Sana and Jalila, 2016), Congo Red (Smaranda et al, 2011), and Acid Red 14 dye (Qu et al, 2008).…”
Section: Sorption Isothermsmentioning
confidence: 80%
See 2 more Smart Citations
“…Freundlich isotherms model also satisfactorily described the sorption of Thioflavin dye in sediments taken from the banks of the Váh River, in Šaľa city, Slovak Republic (Bachratá et al, 2013), and of Basic Yellow X-5GL, Basic Red 13, Direct Blue 86, Vat Yellow 2 and Mordant Black 11 dyes in sediments from the Qinghe River (Liu et al, 2001). Other studies also reported a good correlation of the Freundlich equation with experimental data of dye sorption in soils, such as the Acid Yellow 23 (Dawodu and Akpomie, 2016), Basic Blue 9 (Sana and Jalila, 2016), Congo Red (Smaranda et al, 2011), and Acid Red 14 dye (Qu et al, 2008).…”
Section: Sorption Isothermsmentioning
confidence: 80%
“…The graphs corresponding to Freundlich model adjustments for CM 1 and CM 2 are shown in Figure 3. Considering the chemical composition of the sediment, it can be stated that its organic and inorganic components will significantly affect the sorption capacity (Bachratá et al, 2013). Regarding the organic component, Liu et al (2001) verified a decrease in sorption of the anionic Rev.…”
Section: Sorption Isothermsmentioning
confidence: 94%
See 1 more Smart Citation
“…This fact indicates that metals weakly bound into sediments can be released at slightly acidic conditions. However, in the case of organic xenobiotics bound onto sediments, such as cationic synthetic dyes, they can be released not only at acidic conditions, but more significantly in conditions of less polar solutions, e.g., diluted solutions of alcohols or organic solvents [20].…”
Section: Characterization Of River Sedimentsmentioning
confidence: 99%
“…Our previous papers dealt with mathematical modelling of data characterizing the continuous sorption of cationic dyes thioflavine T (ThT) and malachite green on dried biomass of microalga Chlorella pyrenoidosa [19] as well as with description of synthetic cationic dye ThT sorption onto river sediments under conditions of batch and column systems [20]. The present work is focused on the characterization of benzothiazole cationic dye ThT and thiazine cationic dye methylene blue (MB) sorption onto selected Slovakian river sediments using chemometric approaches including principal component analysis (PCA) and cluster analysis (CA).…”
Section: Introductionmentioning
confidence: 99%